2017
DOI: 10.5468/ogs.2017.60.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Predicting factors for success of vaginal delivery in preterm induction with prostaglandin E2

Abstract: ObjectiveTo evaluate the efficacy and safety of prostaglandin (PG) E2 for preterm labor induction and to investigate the predictive factors for the success of vaginal delivery.MethodsA retrospective cohort study was performed in women (n=155) at 24+0 to 36+6 weeks of gestation who underwent induction of labor using a PGE2 vaginal pessary (10 mg, Propess) from January 2009 to December 2015. Success rates of vaginal delivery according to gestational age at induction and incidence of intrapartum complications suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Secondly, in the context of term gestation, PGF2α concentrations in AF [26] and PTGS2 mRNA expression in amnion [27] abruptly increase before the onset of labor and continuously increase with advancing gestation from 38 weeks to 40 weeks. These findings correspond with the previous results as in the following: (1) Nielsen et al demonstrated that the prevalence of unfavorable Bishop scores (≤5) decreased with increasing GA until 41 weeks during term gestation, ultimately leading to an immediate labor and delivery [15]; and (2) Chow et al found that the levels of CX43 mRNA in myometrial tissue collected from women not in labor significantly increased between 37 and 40 weeks, with a further significant increase occurring during labor [28] It is well-known that preterm gestations with a lower GA have a significantly higher frequency of IAI in both PTL and preterm-PROM [4,6]. Moreover, we previously demonstrated the intensity of IAI continuously increases with decreasing GA during preterm gestation even in the context of the same severity of acute chorioamnionitis [29].…”
Section: Why Are Ptl and Preterm-prom At A Lower Gestational Age (Ga)...supporting
confidence: 92%
See 2 more Smart Citations
“…Secondly, in the context of term gestation, PGF2α concentrations in AF [26] and PTGS2 mRNA expression in amnion [27] abruptly increase before the onset of labor and continuously increase with advancing gestation from 38 weeks to 40 weeks. These findings correspond with the previous results as in the following: (1) Nielsen et al demonstrated that the prevalence of unfavorable Bishop scores (≤5) decreased with increasing GA until 41 weeks during term gestation, ultimately leading to an immediate labor and delivery [15]; and (2) Chow et al found that the levels of CX43 mRNA in myometrial tissue collected from women not in labor significantly increased between 37 and 40 weeks, with a further significant increase occurring during labor [28] It is well-known that preterm gestations with a lower GA have a significantly higher frequency of IAI in both PTL and preterm-PROM [4,6]. Moreover, we previously demonstrated the intensity of IAI continuously increases with decreasing GA during preterm gestation even in the context of the same severity of acute chorioamnionitis [29].…”
Section: Why Are Ptl and Preterm-prom At A Lower Gestational Age (Ga)...supporting
confidence: 92%
“…The frequency of term birth, preterm birth (PTB) (before 37 weeks), late PTB (between 34 and 37 weeks), and early PTB (before 34 weeks) account for about 90%, 10%, 7%, and 3% of all births, respectively [13]. Moreover, an earlier GA is known to make the induction of labor (IOL) more difficult to succeed in preterm [14] and even term pregnant women [15]. Therefore, one can expect that delivery is more difficult in pregnant women at an earlier GA.…”
Section: Why Are Ptl and Preterm-prom At A Lower Gestational Age (Ga)...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the success rate of vaginal delivery was approximately 70%; however, considering that the average rate of cesarean sections in Japan [ 10 , 11 ], including multiparous women, is approximately 19%-25%, the current result is considered not bad at all. In addition, recently, the risk of a cesarean section was reported to be elevated with the use of Propess® in nulliparous women, especially in cases without epidural analgesia during labor [ 12 ]. Although we do not perform epidural anesthesia during the use of Propess® according to the Japanese guidelines [ 8 ], we were relieved that the use of Propess® did not lead to an increase in cesarean sections.…”
Section: Discussionmentioning
confidence: 99%
“…Methods promoting cervical ripening include drugs such as oxytocin and prostaglandin preparations and mechanical methods such as water sac. Dinoprostone is a kind of prostaglandin E 2 preparation, which should be locally applied and can be slowly and continuously released, and it has been clinically proven safe and effective ( 2 ). The disadvantages include that it easily causes excessive uterine stimulation and frequent uterine contractions, thus increasing the probabilities of fetal distress in the uterus and amniotic fluid contamination ( 3 ).…”
Section: Introductionmentioning
confidence: 99%